PENGEMBANGAN MITRA EKONOMI PRODUKTIF SEBAGAI LANGKAH MENGHADAPI DAMPAK COVID 19 DI DESA KESIMAN KERTALANGU DENPASAR BALI - I Wayan Kandi Wijaya; I Wayan Sumarkandia (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic that has hit the world, including Indonesia, has greatly impacted the social and economic life of the community. This also happened and was felt very much for Indonesia, including Bali and its people as business actors in Kesiman Kertalangu Village, as one of the villages in the Denpasar area of ​​Bali. Economically, this impact causes a loss of community income as a result of widespread unemployment and short-term instability. To avoid and deal with these impacts more broadly, it is necessary to carry out continuous and integrated efforts to empower the community's economy with community components. Ngurah Rai University as an educational institution in Bali takes a role and participates in providing solutions to problems as a result of this pandemic. This is done through the Integrated Application Lecture (KAT) as a form of the Tri Dharma of Higher Education, in Community Service through the Community Partnership Program (PKM) in the Development of Productive Economic Partners which is carried out for 1.5 months, for business actors as Foster Partners in Kesiman Village. Kertalangu Denpasar. This program is carried out as a step to deal with the impact of the pandemic on the economic life of the people in the Village.